REFLEKSI PENELITIAN: DARI MASYARAKAT EKSOTIS KE KOMUNITAS KAMPUS DAN CAFE - Yevita Nurti (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2014)
This paper is a reflection of the research in order to exercise anthropological research on the subject Theory, Methods and Practice research at the University of Indonesia. Research with the general theme of campus life and field settings the University of Indonesia, became an interesting experience, especially regarding the crucial issues in contemporary anthropological research, ranging from determining the themes and research plan, to the data collection. How anthropology as a discipline capable of responding to the shifts that occur and require changes to the workings of anthropology, not only change research techniques but also requires the redefinition of the various concepts.